Chemical Approaches for Structure and Function of RNA in Postgenomic Era. (12th January 2012) - Ro-Choi, Tae Suk; Choi, Yong Chun
Abstract : In the study of cellular RNA chemistry, a major thrust of research focused upon sequence determinations for decades. Structures of snRNAs (4.5S RNA I (Alu), U1, U2, U3, U4, U5, and U6) were determined at Baylor College of Medicine, Houston, Tex, in an earlier time of pregenomic era. They show novel modifications including base methylation, sugar methylation, 5 ′ -cap structures (types 0–III) and sequence heterogeneity. This work offered an exciting problem of posttranscriptional modification and underwent numerous significant advances through technological revolutions during pregenomic, genomic, and postgenomic eras. Presently, snRNA research is making progresses involved in enzymology of snRNA modifications, molecular evolution, mechanism of spliceosome assembly, chemical mechanism of intron removal, high-order structure of snRNA in spliceosome, and pathology of splicing. These works are destined to reach final pathway of work "Function and Structure of Spliceosome" in addition to exciting new exploitation of other noncoding RNAs in all aspects of regulatory functions.